Effect of Capital Structure and Growth Opportunity on Firm Value (Case Study on Manufacturing Companies on the Stock Exchange Indonesian Securities) - Burhanuddin Burhanuddin (Universitas Muhammadiyah Palu, 2022)
The calculation results obtained using the multiple linear regression analysis models show that capital structure and growth opportunity simultaneously have a positive and significant influence on firm value. This is supported by the F-counted value of 4,645 at the 0.011 significance level smaller than 0.05, which means that the F-count is greater than the F-table value of 4,645> 3,058. The capital structure is partially insignificant to the company. This is supported by the T-count value of 0.273 at a significance level of 0.785 greater than 0.05, which means that the T-count is smaller than the T-table value of 0.273 <1.976. The growth opportunity is partially negative and significant. This is supported by a T-count value of -3.033 at a significance level of 0.003, smaller than 0.05, which means the amount smaller than the T-table value is -3.033 <1.994.